The Application of Table Sugar and Coconut Water to Enhance the Growth of Post-Acclimatized Moon Orchids (Phalaenopsis Hybrid) - Ratna Nurhayati, Dewi; Sita Sari, Rika (Journal of World Science, 2023)
Research on "The effect of giving granulated sugar and coconut water to increase the growth of moon orchids (Phalaenopsis hybrids)" was carried out from October 2022 to December 2022 at Sinoman Tempel, Sidorejo, Salatiga at an altitude of 500 meters above sea level. This research aims to determine the effect of the concentration of coconut water and granulated sugar on the growth of moon orchids (Phalaenopsis hybrids). The research method used was factorial with a Completely Randomized Design (CRD) consisting of two factors and including three replications. The data from this research were analyzed using the 5% BNJ test. The parameters observed included the number of Leaves at Last Time, Leaf Width, Leaf Length, Number of New Leaves, Root Length, and Live Percentage. There are two research factors, namely coconut water concentration treatment (A) and granulated sugar (B). The results of this study show that 1) Giving coconut water concentrate affects the number of leaves, leaf width, root length and live percentage; 2) Giving granulated sugar treatment has a significant effect on root length and live percentage; 3) The interaction between coconut water concentrate and granulated sugar has an effect on root length, number of recent leaves, and leaf width. 4) Providing the best treatment in the treatment of 75 ml/L coconut water concentrate and 30 gr granulated sugar, which has an effect on the parameters of root length, number of leaves, and survival percentage.